DAMPAK ALIH FUNGSI LAHAN HUTAN MENJADI PERKEBUNANKELAPA SAWIT TERHADAP KONDISI SOSIAL EKONOMI MASYARAKAT - Yessy Syamsul; Budiman Tampubolon; Agus Sugiarto (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
AbstactThis research aimed to find the area distribution and the impacts of forest landto oil palmplantations conversion towards the social and economy conditions of people inDesaSepukLaut from 2012 to 2021. The form of research used was qualitative researchwith case study method. The techniques of data collection included remote sensingtechnique (special methods and characteristics of geography) and triangulationtechnique. The tools of data collection were observation guidelines (field accuracy test),interview guidelines, and public documents. The data were analysed using SIG analysis(Overlay) and Miles and Huberman’s analysis model. The findings showed that (1) thearea distribution of land conversion in DesaSepaukLautin the period 2012 to 2021 was3,902 Ha, and the most dominant change of land conversionwas the conversion of forestland to oil palm plantations in SepukLaut Village reaching to 2035 Ha. In percentage, thetotal area of forest which was converted to oil palm plantations was 52.15%; (2) Thisphenomenon had impacted the education, the kinds of economic activities, and theincome of people within the area.Keywords: Impacts of land conversion, palm oil, social and economy